A novel fault diagnosis method for rotor rub-impact based on nonlinear output frequency response functions and stochastic resonance. (1st September 2020) - Liu, Y.; Li, J.T.; Feng, K.P.; Zhao, Y.L.; Yan, X.X.; Ma, H.
Abstract: The rub-impact fault of the rotor system is the research object in this paper, and the system is modeled by the finite element method. In the process of the study, the high-order harmonic components appear in the output response of the rotor system, which imply that the rotor system is nonlinear. Nonlinear output frequency response functions (NOFRFs) solve nonlinear problems in the frequency domain and explain these nonlinear phenomena. Based on NOFRFs, a method named weighted contribution rate of NOFRFs (WNOFRFs) is used to improve the weak high-order harmonic components proposed by the authors. In this paper, the multi-parameter optimized genetic algorithm is used to calculate the obstacle parameters of the stochastic resonance (SR) which is used to enhance weak signal components. In view of the fact that both WNOFRFs and SR can improve the weak signal components, a new method of weighted contribution rate of NOFRFs incorporating stochastic resonance (WNS) algorithm is proposed in this paper. Based on the algorithm, the variations of index WS show a trend of approximately linear growth, which indicates that index WS has certain advantages for the fault diagnosis of the rotor rub-impact. Graphical abstract: The rotor rub-impact system is established in this paper. By combining stochastic resonance and weighted contribution rate of nonlinear output frequency response functions, the nonlinear characteristics of the rotor rub-impact system are extracted and a new index WS is proposed. The experimental and simulation results indicate that the index is more suitable for the detection of rotor rub-impact fault. Image 1 Highlights: There are nonlinear components in the vibration response of rotor fault system. SR and WNS are Combined to extract these components in the vibration response. The method is more efficiency when the degrees of rub-impact fault are changed.